Karakteristik wirausaha dan sikap keuangan terhadap kinerja UMKM sektor kuliner Kota Denpasar di masa pandemi Covid-19 - I Gusti Agung Krisna Lestari (Universitas Pendidikan Ganesha, 2022)
This research aims to analyze the effect of entrepreneurial characteristics and financial attitudes on the performance of SMEs. The data collection method used in this study was a questionnaire. The number of respondents as the research sample amounted to 302 culinary SMEs in Denpasar City. The analysis technique used is multiple regression analysis. The findings of this study indicate that entrepreneurial characteristics have a significant positive effect on the performance of MSMEs, as well as financial attitudes which have a significant positive effect on performance. Keywords: Entrepreneurial Characteristics, Financial Attitude, MSME Performance